Accuracy of Trained Nurses in Finding Small Bowel Lesions at Video Capsule Endoscopy. (March 2015) - Guarini, Alessandra; De Marinis, Francesca; Hassan, Cesare; Spada, Cristiano; Bruzzese, Vincenzo; Zullo, Angelo
<x xml:space="preserve">Abstract</x> The video capsule endoscopy is an accurate tool to investigate the entire small bowel. Currently, the nurse actively participates in the procedure from patient preparation to the video download, whereas a gastroenterologist interprets the endoscopic findings. However, few studies recently showed high accuracy of nurses in detecting lesions in the small bowel on video capsule endoscopy recordings. This prospective study aimed to assess the ability of experienced and trained nurses in detecting small bowel lesions as compared with gastroenterologists. Forty-six consecutive video capsule endoscopy procedures were analyzed. Overall, the nurse evaluation was highly (95.6%) accurate in detecting small bowel lesions, with a 100% concordance with the gastroenterologist for the relevant findings. In addition, the absence of lesions was confirmed by the endoscopist in all cases classified as negative by the nurse. Data of this study found that trained nurses, with a large experience in endoscopic features, correctly identified small bowel lesions on video capsule endoscopy recordings. Therefore, a trained nurse may accurately select the thumbnails of all mucosal irregularities that may be faster reviewed by the endoscopist for a final diagnosis.